2019
DOI: 10.1186/s13049-019-0607-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of pre-hospital emergency medical services in urban and rural municipalities over a 10 year period: an observational study based on routinely collected dispatch data

Abstract: Background Pre-hospital emergency medical services (EMS) are an integral part of emergency medical care. EMS planning can be achieved by analyzing patterns of use. However, long-term time trends of EMS use have rarely been studied. The objective of this retrospective study was to investigate utilization patterns over a ten year period, and to compare utilization trends between urban and rural municipalities and between events with and without prehospital emergency physician (PEP) dispatch. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 23 publications
(22 reference statements)
4
22
0
5
Order By: Relevance
“…7,14,21,22 F I G U R E 1 Flow chart showing analysis population. 1 On-site resolution: either the ALS physician has been able to stabilize the patient on the scene and his/her condition was no longer serious or once the patient has been evaluated it was found that he/she does not needed any type of manoeuvre or be transferred to the ED. 2 Risk on scene: situations with weapons on the scene, aggressive patients, traffic accidents with risk of fire or explosion, etc In order to study pLA triggers or cut-off points we used already described thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,14,21,22 F I G U R E 1 Flow chart showing analysis population. 1 On-site resolution: either the ALS physician has been able to stabilize the patient on the scene and his/her condition was no longer serious or once the patient has been evaluated it was found that he/she does not needed any type of manoeuvre or be transferred to the ED. 2 Risk on scene: situations with weapons on the scene, aggressive patients, traffic accidents with risk of fire or explosion, etc In order to study pLA triggers or cut-off points we used already described thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency medical services (EMS) deal on the scene and en route with complex patients suffering from acute pathologies usually presenting several comorbidities. 1 Such scenarios are faced by the EMS workers with very limited diagnostic information which hampers their clinical decisions. 2 There is today a growing interest in detecting bed-side situations which require rapid clinical responses.…”
Section: Introductionmentioning
confidence: 99%
“…Demand for EMS in Germany is rising, with an increase of 105% since 2001 1. An increase in EMS activation in both, urban and rural regions of Bavaria was observed over the past 10 years 2. Rising use of EMS and emergency departments (ED) contributes to ED crowding and scarcity of hospital admission capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a "transport" itself and especially "transports to hospitals" seem to be inadequate objective indicators: Germany's rate of EMS transports per case is higher than in other European countries [26,27] and the U.S. [28]. Analysis of Bavarian dispatch data hint that about 20% of the patients are not transported to a hospital [29]. Schmiedel and Behrendt [2] estimated for Germany that 9% without and 6% of all prehospital emergency care cases with physicians are cases without transports, procedures or being cancelled prior to arrival.…”
Section: Discussionmentioning
confidence: 99%